Employee Well-Being Programs and Their Impact on Productivity and Competitive Advantage - Novaldo, Gregorius; Strada, Dela Rosari (Universitas Sains dan Teknologi Komputer, 2025)
The intensifying competitive business landscape forces organizations to adopt strategic approaches that enhance performance and employee well-being as a high-value human capital asset. This study aims to investigate the impact of employee well-being programs on competitiveness and productivity in service and manufacturing companies in Indonesia. The sequential explanatory design mixed-methods research design was used with 200 survey respondents and 10 qualitative informants. Quantitative data were tested with multiple regression analysis using SPSS, and qualitative responses with thematic analysis. The findings indicate that employee well-being has a significant and positive influence on productivity (β = 0.62; p < 0.05) and also contributes to competitive advantage directly and indirectly through productivity (β = 0.53; p < 0.05). Descriptive statistics indicate that employees opine that well-being initiatives enhance their work performance. Qualitative findings also establish that organizational support of physical and mental well-being increases work concentration and psychological engagement. The novelty of this research is in its all-encompassing empirical model incorporating well-being, productivity, and competitiveness within a developing economy context, providing managerial wisdom on strategic HR practices to augment long-term business competitiveness.